2016
DOI: 10.1063/1.4943372
|View full text |Cite
|
Sign up to set email alerts
|

Guiding ab initio calculations by alchemical derivatives

Abstract: We assess the concept of alchemical transformations for predicting how a further and not-tested change in composition would change materials properties. This might help to guide ab initio calculations through multidimensional property-composition spaces. Equilibrium volumes, bulk moduli, and relative lattice stability of fcc and bcc 4d transition metals Zr, Nb, Mo, Tc, Ru, Rh, Pd, and Ag are calculated using density functional theory. Alchemical derivatives predict qualitative trends in lattice stability while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…First order terms are firmly established for all variables through the Hellmann-Feynman theorem for changes in nuclear positions (to relax or run ab initio molecular dynamics 42 ), and charges. 22,27,32,33,36,37,[43][44][45] The derivative with respect to N is related to ionization potential and electron affinity by virtue of Koopman's and Janak's theorem, 46 and exhibits the well established derivative discontinuity at integer N , 47,48 so important for the construction of improved exchangecorrelation approximations. 49 Some elements in the Hessian, molecular vibrational normal modes, or the second order derivative of the electronic energy with respect to the number of electrons is the chemical hardness, introduced by Parr and Pearson.…”
Section: Theorymentioning
confidence: 99%
“…First order terms are firmly established for all variables through the Hellmann-Feynman theorem for changes in nuclear positions (to relax or run ab initio molecular dynamics 42 ), and charges. 22,27,32,33,36,37,[43][44][45] The derivative with respect to N is related to ionization potential and electron affinity by virtue of Koopman's and Janak's theorem, 46 and exhibits the well established derivative discontinuity at integer N , 47,48 so important for the construction of improved exchangecorrelation approximations. 49 Some elements in the Hessian, molecular vibrational normal modes, or the second order derivative of the electronic energy with respect to the number of electrons is the chemical hardness, introduced by Parr and Pearson.…”
Section: Theorymentioning
confidence: 99%
“…The rigorous definition of the chemical compound space (CCS), using insights from the grand‐canonical treatment of open systems and the so‐called conceptual density functional theory (DFT), has opened a fruitful avenue of research in the field of rational compound design . This allows us, in principle, to optimize a given property by analyzing its variation in response to changes in the molecular composition, that is, by navigating in CCS.…”
Section: Introductionmentioning
confidence: 99%
“…To conclude on an optimistic note, we should mention that there are nontrivial (exact) results of linear interpolating Hamiltonians within certain small families of systems, for example, the result of Von Lilienfeld for Hydrogenic atoms . Additionally, recent studies have demonstrated that one can find rules according to which the predictions made using the alchemical framework can reach significant accuracy . This shows that it is likely that for small families of molecules, analogous (approximate, but accurate) alchemical transformation formulas can be found by numerical fitting.…”
Section: Introductionmentioning
confidence: 99%
“…It seems natural that the exploration of chemical space has improved by merging these tools with visual data analysis techniques; or the combination of quantitative structure–activity relationship (QSAR) methods with computational chemistry calculations . Inverse quantum chemical approaches are becoming popular to find a chemical structure departing from a set of desired properties; an outstanding example of these kind of methodologies is the alchemical potential approximation …”
Section: Introductionmentioning
confidence: 99%